PERSEPSI GURU PAMONG TERHADAP KOMPETENSI MAHASISWA PENGENALAN LAPANGAN PERSEKOLAHAN (PLP) PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU DI SMA KOTA PEKANBARU TAHUN 2019 - Devi Yustria Leha; Suarman Suarman; Mujiono Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the perceptions of teachers tutors to competence of PLP students of economic education FKIP Riau University at Pekanbaru City High School in 2019. Competencies reviewed include pedagogical competence, professional competence, personality competence, and social competence. This type of research is a quantitative descriptive study. The data collection technique used was a Likert scale questionnaire and documentation. The data analysis technique used was descriptive statistics. Based on the teacher's perceptions of 25 PLP students, the results of the study showed that, the PLP students' pedagogical competence was in the Good category with a percentage of 83.02%, professional competence was in the Very Good category with a percentage of 84.5%, personal competence was in the Very Good category with a percentage 88.2%, and social competence is in the Very Good category with a percentage of 87.87%. Based on these results, the competence of PLP students in economic education is in the Very Good category with an average percentage of 85.90%. Furthermore, students are expected to maintain and improve several aspects of perceived competence such as the ability to understand the characteristics of students, develop and apply learning materials creatively and innovatively.Key Words: Perception, Teacher Competence, Introduction To The School Field.